Effect of Home Physiotherapy on Balance and Dynamic as Well as Kinematic Movement Characteristics of the Dominant Hand for People with Parkinson`s Disease (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Parkinson’s disease (PD) is a disease of the elderly, characterized by motor symptoms (resting tremor, bradykinesia, rigidity, and postural instability) when the extrapyramidal system lacks dopamine. Studies have shown that physiotherapy together with the usual medication used to treat PD can slow down the increasing immobility.Research aim was to assess the effect of home physiotherapy on balance and dynamic as well as kinematic movement characteristics of the dominant hand for people with Parkinson’s disease.Research methods. Research group consisted of 8 patients with PD, stage 1–2 of the disease, the symptoms of which were expressed on the right hand. The study was conducted using Fullerton balance test and the human arm and leg movement Dynamic Parameter Analyser DPA-1.Research results. Balance as well as kinematic and dynamic characteristics of movements for patients with PD statistically significantly improved (p < 0.05) after the physiotherapy exercise cycle at home.Discussion  and  conclusions.  After  physiotherapy,  coordination  of  the  dominant  hand  for  patients  with  PD significantly improved: reaction time became shorter, maximum and average task speed increased, balance improved statistically  significantly. The  results  showed  that  physiotherapy  at  home  was  an  effective  and  reliable  way  for patients with PD to train their balance as well as kinematic and dynamic characteristics of their movements.Keywords: physiotherapy, Parkinson’s disease, reaction time.